Survival and immune response of white shrimp Litopenaeus vannamei following single and concurrent infections with WSSV and Vibrio parahaemolyticus. Issue 92 (September 2019) - Pang, Huanying; Wang, Gang; Zhou, Shihui; Wang, Junlin; Zhao, Jichen; Hoare, Rowena; Monaghan, Sean J.; Wang, Ziling; Sun, Chengbo
Abstract: The survival and immune responses of Litopenaeus vannamei were evaluated during white spot syndrome virus (WSSV) or Vibrio parahaemolyticus single and concurrent infections. The mortality, WSSV load, activities of 4 immune enzymes: acid phosphatase (ACP), alkaline phosphatase (AKP), peroxidase (POD) and superoxide dismutase (SOD), and the transcription of Evolutionarily Conserved Signaling Intermediate in Toll pathways of L.vannamei (LvECSIT) were quantified at 0, 3, 6, 12, 24, 48, 72 and 96 h post-infection (pi). The results showed: (i) the cumulative mortality of the co-infection group (WSSV and V. Parahaemolyticus 83%) was significantly lower than the WSSV infection group (97%) (P < 0.05) at 96 hpi; (ii) copies of WSSV in the co-infection group were significantly lower than that of the single infection group from 24 to 96 hpi (P < 0.05); (iii) ACP, AKP, POD and SOD activity in the gills of the co-infection group was higher than that of the WSSV group at12, 48 and 96 hpi (P < 0.05).The expression of LvECSIT mRNA in the co-infection group was significantly higher than in the WSSV infection group from 12 to 72 hpi (P < 0.05).The results indicate that proliferation of WSSV is inhibited by V.parahaemolyticus infection. In addition, infection with WSSV alone causes a significant reduction in some immune responses of shrimp than co-infection with WSSV and V.parahaemolyticus occurs at 26 °C. Third, LvECSIT, an essential member of TLR signaling pathway might play a crucial role in shrimp defense against WSSV – Vibrio co-infection. Highlights: Shrimp in co-infection groups suffered lower mortality than WSSV group. The amount of WSSV in co-infection group was lower than in WSSV group. ACP and AKP enzyme activity can be used as indicators to co-infection. The transcription level of LvECSIT was up-regulated in co-infection groups.